KONSEP KARTU KREDIT (BITHAQAH I’TIMAN) SEBAGAI ALAT PEMBAYARAN DALAM EKONOMI ISLAM - Mujiatun Ridawati (Al-Qardhu, 2022)
This article discusses the concept of a credit card as a means of payment in Islamic law. There are two main problems studied, namely (1) the conception of Shariah credit cards (alternatives) in Sharia Banking that can accommodate the needs of the community that are appropriate and do not conflict with Islamic Sharia; (2) the opinion of the scholars regarding the use of credit cards. The two problems were studied using a library approach by using books, magazines, journals and several other scientific works as primary sources. After conducting research, the authors found that Islamic credit cards can only be accessed for transactions on goods that have been determined with halal criteria. There are several opinions of scholars regarding the law on the use of credit cards related to the problems above. There are scholars who allow and there are also those who forbid based on their respective foundations. The MUI National Sharia Council stated that the use of sharia credit cards is allowed as long as it fulfills the provisions, and if it violates these provisions, the law will become illegal.